Vascular β-amyloid potentially colocalises with phosphorylated tau in cerebral amyloid angiopathy - Li-Kai Tsai; Hsin-Hsi Tsai; Bo-Ching Lee; Chia-Ju Liu; Pu-Tien Chiang; Ya-Chin Tsai; Syu-Jyun Peng (Stroke and Vascular Neurology)
Background Tau pathology is observed in cerebral amyloid angiopathy (CAA) and is related to cognitive impairment and neurodegeneration. However, the relationship between tau pathology and amyloid accumulation in the vasculature is unknown. We aimed to assess if regional associations exist between vascular amyloid and tau protein in sporadic CAA.Method We assessed cerebral amyloid and hyperphosphorylated tau in patients with probable CAA or Alzheimer’s disease (AD) using 11C-Pittsburgh compound B (PiB) and 18F-T807 positron emission tomography (PET). PET data for each region of interest were extracted using an automated anatomical labelling atlas. We generated correlation matrices to investigate the regional correlations between PiB and T807 uptake, which were further adjusted for multiple comparisons. We evaluated if the severity of regional cortical superficial siderosis (cSS) mediates these associations.Results 67 patients with CAA (38 with intracerebral haemorrhage and 29 with cognitive impairment) and 21 patients with AD were included. Significant correlations between amyloid and tau PET uptake were observed in regions of interest for the temporal, parietal and occipital lobes in CAA (adjusted p<0.05); these correlations were not observed in AD. In CAA, the severity of regional cSS correlated positively with T807 uptake in the temporal (β=0.108, 95% CI 0.030 to 0.186, p=0.007) and occipital lobes (β=0.088, 95% CI 0.008 to 0.168, p=0.032). Regional cSS showed no mediating effect on the association between PiB and T807 in the occipital and temporal lobes.Conclusions In CAA, tau pathology exhibits significant regional in situ correlations with amyloid deposition in the posterior brain, which suggests a distinct pathophysiology to AD.